Moisture Regime, Aridity and Droughts in The Arid Region of Andhra Pradesh - Victor, U S; Srivastava, N N; Rao, B V.Ramna (Annals of Arid Zone, 2016)
Weekly water balance computation were carried out for .the years 1911-85 considering different avail'able water holding capacities ranging from 25 to 200 mm to examine the ti*tent to which the moisture regime and aridity are dependent on water holding capacity of the soil. The analysis reveals that the aridity is accentuated by the shallowness of the soil coupled with low rainfall in this region. The number of years with drought was found to vary from 3 to 6 per decades. The yields of groundnut and kodomil1etlwere reduced by 25 and 50 percent during the years with large and severe droughts respectively. The water harvesting may be useful either for late sown kharif crops or for establishment of tree plantations in this region.